BENTUK, MAKNA, DAN REFLEKSI SOSIOKULTURAL PADA RESTORAN BERKONSEP TRADISIONAL DI MALANG RAYA - Kingkin Puput Kinanti; Endang Setyowati; Ari Nugrahani (UPT Bahasa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study investigates the naming of traditional-concept restaurants and culinary menus in Greater Malang. The objectives are threefold: to analyze the forms of names at the phonological, morphological, and syntactic levels; to identify their associative meanings; and to reveal their sociocultural reflections. The study highlights the importance of naming practices, as names embody thoughts, ideas, and philosophical values. In the context of traditional restaurants, names serve not only as commercial labels but also as markers of cultural preservation amidst the strong influence of modernization. A descriptive qualitative research was used which data were collected from restaurant names and menus through observation, interviews, and documentation from online media such as Instagram and Google Maps. The data were analyzed using an anthropological linguistic approach, which situates language within its social and cultural contexts. The findings reveal that the naming of traditional-concept restaurants in Greater Malang contains both denotative and associative meanings. Associative meanings highlight humor, nostalgia, grandeur, and geographical identity. The use of Javanese terms reflects pride in tradition and reinforces values of egalitarianism, togetherness, and rural simplicity. Furthermore, the blending of local expressions with foreign terms illustrates an acculturation between Javanese tradition and global modernity, positioning naming practices as both a communication strategy and a representation of cultural identity.